MANAJEMEN STRATEGIK KEPALA SEKOLAH DALAM PENGEMBANGAN LINGKUNGAN SEKOLAH YANG KONDUSIF (Irfani (e-Journal), 2022)
This study aims to determine the principal's strategic management in developing a conducive school environment. The research method used is a descriptive quantitative research using a questionnaire instrument with a sample of 20 teachers. The results of the study, namely the management of the principal's strategy for teachers in developing a conducive school environment at SDN 2 Gorontalo were in the good category with an average percentage of around 75.67%. This percentage gain is an accumulation of the dimensions of the principal's planning strategy in developing a conducive school environment which is in the good category with a percentage of 75%, the dimensions of the principal's implementation strategy in developing a conducive school environment are in the good category with a percentage of 77%, and follow-up strategies principals in developing a conducive school environment are in the good category with a percentage of 75%. The position of the principal when acting as the principal is very strategic or supportive to create a school environment. Because, the core element of the organizational environment is the relationship between school personnel, in the role of the principal when he becomes the principal it is stated that he has a function in realizing harmonious human relations to foster and develop cooperation between personnel.